2013
DOI: 10.1016/j.neuropsychologia.2013.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Distinct neuroanatomical bases of episodic and semantic memory performance in Alzheimer’s disease

Abstract: Alzheimer's disease (AD) neurofibrillary pathology begins in the medial perirhinal cortex (mPRC) before spreading to the entorhinal cortex (ERC) and hippocampus (HP) in anterior medial temporal lobe (aMTL). While the role of the ERC/HP complex in episodic memory formation is well-established, recent research suggests that the PRC is required to form semantic memories of individual objects. We aimed to test whether commonly used clinical measures of episodic and semantic memory are distinctly associated with ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 61 publications
6
67
0
1
Order By: Relevance
“…Similar findings were reported by Wilson et al [42], who showed that an average of three semantic memory tests (i.e., verbal fluency, Boston Naming Test, and a measure of reading recognition) was affected earlier than episodic memory performance (76 versus 63 months, respectively) in a group of 462 NC-AD patients. Since the mPRC presumably codes for semantic object memories [14,16], the findings of Amieva et al [32] and Wilson et al [42] are in line with the pattern of cortical NFT pathology in AD, which affects the mPRC before the ERC in the preclinical course of AD [5].…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Similar findings were reported by Wilson et al [42], who showed that an average of three semantic memory tests (i.e., verbal fluency, Boston Naming Test, and a measure of reading recognition) was affected earlier than episodic memory performance (76 versus 63 months, respectively) in a group of 462 NC-AD patients. Since the mPRC presumably codes for semantic object memories [14,16], the findings of Amieva et al [32] and Wilson et al [42] are in line with the pattern of cortical NFT pathology in AD, which affects the mPRC before the ERC in the preclinical course of AD [5].…”
Section: Discussionmentioning
confidence: 57%
“…However, many wellestablished clinical neuropsychological tests used in current longitudinal studies are more meta-cognitive in nature, lacking the anatomical specificity to target the PRC. For example, Hirni et al [16] demonstrated that both clinical tests of episodic memory and semantic object memory significantly predicted ERC/HP and PRC atrophy. However, linear regression analyses differentiated the relationships between PRC integrity and semantic memory functioning, and ERC/HP integrity and episodic memory functioning: when the opposing memory performance was controlled, episodic memory performance was associated with ERC/HP but not PRC integrity, whereas semantic memory was associated with both PRC and ERC/HP integrity [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies suggest the involvement of the EC in learning and memory. [31][32][33] The EC serves as a gateway between the hippocampus and frontal aspects of the neocortex, playing a central role in memory retrieval. 31 In our sample of mTBI/PTSD subjects, the EC was unexpectedly found to be enlarged, compared with mTBIonly subjects.…”
Section: Discussionmentioning
confidence: 99%
“…34 Additional evidence for the role of the lateral cortex in working memory is the higher rate of memory decline following anterior temporal lobectomy compared with selective amygdalohippocampectomy. 18 The perirhinal cortex and temporal lobe white matter tracts are involved in semantic memory processing, 23 as are the middle and inferior temporal gyri. 9 Traditional surgical approaches can compromise the cortex and fiber tracts subserving memory function, resulting in progressive white matter atrophy up to a year following surgery 16 and impeding cognitive recovery.…”
Section: 4350mentioning
confidence: 99%